PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN TEROPONG PECAHAN DI KELAS IV SDN 08 PONTIANAK UTARA - Ismail, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to describe improving learning outcome student in learning matematika by using binoculars fragment in class IV primary school Negeri 08 North Pontianak. The method used in this research is descriptive method and type of research is a class act. Subject research is teacher and student total 33 students in class IV B primary school Negeri 08 North Pontianak.. The implementation of this class action is carried out 3 cycles. The results obtained are the ability of teachers in preparing the RPP with an average score of cycle 1 of 2.30, on cycle 2 of 3.05, and in cycle 3 of 3.83. The ability of teachers to implement the average score learning cycle 1 of 2.43, the cycle 2 of 3.14, and on the 3rd cycle of 3.88. While the result of student learning cycle 1 is 55,76, cycle 2 is 70,30, and cycle 3 is 90,91. It using binoculars fragment gave effect on student learnig outcomes. Keywords : Learning Outcomes, Mathematic, binoculars fragment.